PENGEMBANGAN MODUL PEMBELAJARAN LITERASI SAINS BERBASIS KURIKULUM MERDEKA PADA MATERI FOTOSINTESIS DI SEKOLAH DASAR - Yuni Nurfauziah; Akhmad Nugraha; Agnestasia Ramadhani Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Science literacy is an ability that must be achieved by students through science learning in elementary school. Based on PISA scores (2022) Indonesian students still have low science literacy skills. The low level of science literacy is partly due to the selection of teaching materials. Teaching materials used by educators in the Implementation of Kurikulum Merdeka have not been able to facilitate students' science literacy skills, especially on photosynthesis material. This study aims to produce a product in the form of a learning module that can facilitate science literacy skills in photosynthesis material. The method used is Research and Development (R&D) by referring to the development stages of the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The results showed that based on the results of expert validation, the material expert validation results obtained an average percentage of 81.5% with very feasible criteria, module experts get an average percentage of 95.5% with very feasible criteria, and assessment experts get an average percentage of 100% with very feasible criteria. Implementation was carried out in two stages. The results of the first phase of the trial from the learner response questionnaire obtained an average percentage of 83% and the educator response questionnaire of 87% with very feasible criteria. The results of the second trial of the learners' questionnaire obtained an average percentage of 85% and the educator's response questionnaire of 93% with very feasible criteria. Therefore, the learning module product in this development is declared very feasible to be used in the learning process in elementary schools.